Transitional Housing and the Family Capacity Building Planner: An Urban Graduation Approach for Improving the Mental Health and Well-Being of Poor Households in Hong Kong - Siu-Ming Chan; Heng Xu; Yuen-Ki Tang; Kim Kwok; Ka-Man Leung (Buildings, 2025)
(1) Objective: This study aims to investigate how transitional housing and the FCBP programme function as infrastructure for improving mental health and building family capacity among low-income households in Hong Kong, introducing the Urban Graduation Approach, adapted from the rural Graduation Approach, as an adaptation of proven poverty-alleviation strategies to urban contexts. (2) Methods: We conducted in-depth, semi-structured interviews with 24 residents of transitional housing participating in the Family Capacity Building Planner (FCBP) programme, an important component of The Hong Kong Jockey Club’s Trust-Initiated Project—JC PROJECT LIFT in uplifting residents and enhancing their overall well-being, analysing their experiences through thematic analysis focused on housing transitions, service utilisation, and well-being outcomes. (3) Results: Transitional housing provides essential infrastructure for improving residents’ well-being through both physical improvements and integrated support services. Participants reported significant mental health benefits, with reductions in stress and anxiety directly attributed to increased living space, improved privacy, and better environmental conditions. The FCBP programme functions as soft infrastructure that enables residents to access support networks, enhance family relationships, develop employment skills, and build self-efficacy. Together, these interventions address the multidimensional challenges of urban poverty while fostering sustainable improvements in residents’ capacity to achieve housing security and economic stability. (4) Conclusions: The integration of transitional housing with capacity-building services demonstrates the effectiveness of the Urban Graduation Approach in addressing urban poverty. This model highlights the importance of viewing housing not merely as a physical shelter but as a comprehensive infrastructure for well-being that combines spatial improvements with targeted social support. Policy implications include the need for the continued development of integrated housing models and the scaling of successful elements to broader social housing programmes.